Judicial Reform for Justice, Human Rights, Building a Rule-of-law State and International Integration in Vietnam in the Current Period - Kien, Tuong Duy (VNU Journal of Science: Legal Studies, 2021)
Judiciary, albeit being understood in the broadest sense of the word (i.e. activities undertaken by all the state agencies in charge of investigation, prosecution, adjudication, law enforcement, including judicial support institutions) or in the narrowest sense (i.e. only the adjudication of the courts), has a direct and decisive impact on political life, rights, freedoms and interests of individualss/citizens. In order that human rights and freedoms are respected and protected, it is necessary to promote judicial reform (making the judiciary be constantly clean and strong, serving public interest and abiding law, so that it can be the mainstay of justice). Therefore, successful implementation of judicial reform will contribute to protecting justice, human rights, and successful protection of justice, human rights will be a critical determinant of successful building rule-of-law state and international integration. For these reasons, the 13th National Party Congress has required the judiciary to have responsibility for protecting justice and human rights. This is an important and consistent guideline for reforming the judiciary in Vietnam up to 2030, with a vision to 2045. This article makes an in-depth analysis of the objective requirements for protecting justice, human rights in the context of building a socialist rule-of-law state and international integration; and the relationship and interdependence between protection of justice, human rights and judicial reform. The article argues that successful protecting justice and human rights will be an important factor for the success of building a rule-of-law state and international integration in Vietnam. Keywords: Justice, human rights, judicial reform, rule-of-law state, international integration.